DAMPAK INTERAKSI GLOBAL TERHADAP KUALITAS KOMUNIKASI VERBAL SISWA SD - Andini Aulia Zahra; Selly Meita Safira, Zahrah Umi Hasanah, Melita Amanda, Yoga Fernando Rizqi (CV. ADIBA AISHA AMIRA, 2024)
This research aims to find out how global interaction affects the quality of elementary school students' verbal communication. This study was carried out by collecting data through book and journal literature studies. The research results show that global interaction through information and communication technology (TIC) influences the social interaction patterns of elementary school students. Students who use gadgets a lot and interact via social media rely more on social media communication and instant messaging than face-to-face interaction. Excessive use of gadgets is also associated with impaired verbal communication. These findings help to better understand how global interactions can influence the way students interact with others. The implications of this research can be used as a basis for developing more effective strategies to deal with the impact of global interactions on the quality of elementary school students' verbal communication